Research trends and frontiers in rehabilitation after total knee arthroplasty: based on bibliometric and visualization analysis - Runkai Zhao; Haichao Ren; Pengcheng Li; Menglin Fan; Runzhi Zhao; Te Liu; Yan Wang; Quanbo Ji; Guoqiang Zhang (Journal of Orthopaedic Surgery and Research)
Abstract Background Total knee arthroplasty (TKA) is an effective treatment for end-stage knee osteoarthritis, and postoperative rehabilitation is crucial. However, a comprehensive bibliometric analysis of this area has yet to emerge. This study aims to visualize the research trends in postoperative rehabilitation after TKA through bibliometric analysis and explore current research frontiers and hotspots. Methods Publications related to postoperative rehabilitation following TKA were identified and extracted from the Web of Science Core Collection (WoSCC) database. CiteSpace and VOSviewer were used for bibliometric and visualization analysis. Results From January 1, 2000, to December 31, 2022, a total of 1,422 articles on TKA postoperative rehabilitation were identified from the database. The number of publications and citations showed steady growth during this period. The United States was the major contributor in this field, with the University of Colorado being the most active institution domestically. J Arthroplasty ranked first in both publication volume and total citations among all journals. Stevens-Lapsley, JE, and Mizner, RL were the two most influential authors. Reference and keyword analyses suggest that remote or home-based rehabilitation, the development of novel prehabilitation techniques, and pain management hold significant research potential, constituting current research hotspots. Conclusion This study quantitatively identified and assessed the current research status and trends in perioperative rehabilitation management for TKA through bibliometric and visualization analyses. It provides essential information for scholars in the field of TKA postoperative rehabilitation research, highlighting key research frontiers and trends.